Development banking in India - Saksena, R. M. (Bombay : Vora, 1970)
This book is intended to fill up the much felt gap in the sphere of literature on development banking, namely, the absence of any book dealing exhaustively with the structure and problems of development banking in India.
Includes index.
Includes bibliographical references: p. [297]-304
usc 28/01/2019
Loans
Keywords: Development banks; Banks and banking; India